Post-Truth and Political Discourse - Block, David; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Pivot, 2019)
In this book David Block draws on analytical techniques from Critical Discourse Studies to critically investigate truth, truths, the propagation of ignorance and post-truth. Focusing on corrupt discourses and agnotology, he explores the role of anti-intellectualism, emotion and social media in the cultural creation, legitimisation and dissemination of ignorance. While encompassing analysis of discourses on Donald Trump, Brexit, climate change and the Alt-Right, Block furthers our understanding of this global phenomena by providing a revealing analysis of political communications relating to corruption scandals involving the Spanish conservative party. Through an innovative theoretical framework that combines critical discourse and discourse historical approaches with nuanced political analysis, he uncovers the rhetorical means by which esoteric truths and misleading narratives about corruption are created and demonstrates how they become, in their turn, corrupt discourses. This original work offers fresh insights for scholars of Discourse Analysis, Sociolinguistics, Politics, Cultural and Communication Studies, and will also appeal to general readers with an interest in political communication and Spanish politics. David Block is ICREA Research Professor in Sociolinguistics at the University of Lleida, Spain. He has published on a variety of language-related topics, which he examines drawing on scholarship in Marxist political economy and sociology. His books include Social Class in Applied Linguistics (2014) and Political Economy and Sociolinguistics (2018).
Chapter 1: Introduction -- Chapter 2: Post-truth Ruminations -- Chapter 3: Political Discourses, Corrupt Discourses -- Chapter 4: Conclusion.
Keywords: Linguistics -- Methodology; Communication in politics; Sociolinguistics; Political sociology; Knowledge, Sociology of; Ethnology; Culture; Research Methods in Language and Linguistics; Political Communication; Sociolinguistics; Political Sociology; Sociology of Knowledge and Discourse; Regional Cultural Studies